Technique comparison of male and female hammer throwers - Konz, S. M.; Hunter, I. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Distinct anthropometric differences occur between the sexes throwing the hammer that affect technique. No literature statistically compares the differences between male and female hammer throwers. The aim of this study was to determine the hammer throwing technique differences occurring between genders. The performances of 16 male and female throwers at the 2003 World Athletic Final and 13 male and female throwers from the 2003 USA Track and Field Nationals were examined. The best throw of each athlete was digitized and analyzed using the Peak Motus 8.2 motion analysis system. Results revealed that athlete mass, athlete height, velocity at release, timing components, and centripetal force were different between sexes.